1985
DOI: 10.2307/1941327
|View full text |Cite
|
Sign up to set email alerts
|

Forest Litter Decomposition in Relation to Soil Nitrogen Dynamics and Litter Quality

Abstract: Decomposition and changes in nitrogen and organic—chemical content of six types of forest litter were studied for 2 yr in five adjacent Wisconsin forests. The five forests were floristically dissimilar, being dominated respectively by sugar maple (Acer saccharum), white oak (Quercus alba), bigtooth aspen (Populus grandidentata), white pine (Pinus strobus), and hemlock (Tsuga canadensis), Nitrogen mineralization rates in the five stands ranged from 29 to 125 kg°ha—1°yr—1. Decomposition rates of transplanted sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
253
2
9

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(283 citation statements)
references
References 21 publications
19
253
2
9
Order By: Relevance
“…Although linear increases in Nand P concentrations were reported at the early stages of decomposition (McClaugherty et al 1985;Berg and McClaugherty 1989), there seemed to be a limit for the increase. N concentration had reached a plateau in the H layers, especially in the case of the broad-leaved forests and some sites even showed a decrease in N concentration in the H layers (APPENDIX).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although linear increases in Nand P concentrations were reported at the early stages of decomposition (McClaugherty et al 1985;Berg and McClaugherty 1989), there seemed to be a limit for the increase. N concentration had reached a plateau in the H layers, especially in the case of the broad-leaved forests and some sites even showed a decrease in N concentration in the H layers (APPENDIX).…”
Section: Discussionmentioning
confidence: 91%
“…In general, the concentrations of nutrients in the fresh litter of broad-leaved species are higher than those of coniferous species (Morita 1972), and broad-leayed litter usually decomposes more quickly than coniferous litter (Williams and Gray 1974). Chemical properties are one of the important factors controlling litter decomposition (Berg and Staaf 1980;McClaugherty et al 1985). This concept suggests that fertility and characteristics of soils may be affected if dominant species of vegetation and litter composition change due to changes in forest management or global climatic conditions.…”
mentioning
confidence: 99%
“…Numerous studies have shown that the lignin:N ratio can be used as a predictor of organic matter decomposition rates (Melillo et al 1982(Melillo et al , 1989McClaugherty et al 1985;Laishram and Yadara 1988;Aber et al 1990). Other studies have shown that the lignin:N ratio is only useful for the prediction of organic matter decomposition rates when comparing decomposition of litter types that have similar chemical compositions (Hendrickson 1985;Taylor et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…To complicate matters further, shifts in microbial composition are just one route by which environmental change impacts leaf litter decomposition. Decomposition rates are also influenced directly by abiotic conditions and changes in litter quality (for example, Mcclaugherty et al, 1985;Cotrufo et al, 1994;Cleveland et al, 2014).…”
Section: Introductionmentioning
confidence: 99%